ChemInform Abstract: Bidentate, Monoanionic Auxiliary‐Directed Functionalization of Carbon‐Hydrogen Bonds. Issue 25 (5th June 2015) - Daugulis, Olafs; Roane, James; Tran, Ly Dieu
Abstract: Review: 75 refs.